Processing Body Image on Social Media: Gender Differences in Adolescent Boys’ and Girls’ Agency and Active Coping - Mahon, Ciara; Hevey, David (Frontiers in Psychology, 2021)
Although scholars continue to debate the influence of social media on body image, increased social media use, especially engaging in appearance-related behaviors may be a potential risk factor for body dissatisfaction in adolescents. Little research has investigated how adolescents process appearance-related content and the potential strategies they use to protect body image perceptions on social media. To investigate coping strategies used by adolescents, four qualitative focus groups were conducted with 29 adolescents (23 girls) aged 15-16 years (M=15.31, SD=.47) in mixed-gender Irish secondary schools. Thematic analysis revealed that adolescents employed many different behavioral strategies such as avoiding negative content and selecting positive content. Cognitive processing strategies such as critically evaluating body-related content, psychologically distancing from and positively reframing challenging content were also used, although less frequently. Boys appeared to exhibit greater positive agency over their bodies and social media use and tended to use more active coping styles than girls. Efforts to promote body image on social media such as body positive pages and exposing artificial social media content were considered limited in their effectiveness. These findings inform efforts to protect and promote adolescent body image on social media.